Geochemical investigation of the lower Cambrian mineralised black shales of South China and the late Devonian Nick deposit, Canada - Pagès, A.; Barnes, S.; Schmid, S.; Coveney, R.; Schwark, Lorenz; Liu, W.; Grice, Kliti; Fan, H.; Wen, H. (Elsevier Science BV, 2018)
© 2018 Lower Cambrian (Tommotian) black shales of the Niutitang Formation, South China, host a thin accumulation (5–20 cm) of Ni, Mo, platinum group elements (PGE)-Au, Ni, As, Zn, Cu, V and rare earth elements (REE). Of all known deposits, the late Devonian Ni-Mo-PGE sulphide horizon in black shales of the Nick deposit, Selwyn Basin in Canadian Yukon, presents the strongest similarity with the Niutitang Formation polymetallic layer. In the present study, samples of the mineralised layer and host shales in South China from two mine sites (Zunyi and Sancha) were investigated in order to further characterise the prevailing redox conditions and mechanisms involved in the metal concentration process at both sites. Additional comparison with the Nick deposit mineralised layer was also undertaken. Bulk geochemical analysis (including PGE analysis) were conducted on all samples, along with μm-scale investigation of metal distributions and associations by X-ray fluorescence (XRF) mapping and Synchrotron XRF mapping. The comparison of the two sites from South China highlights strong similarities in metal enrichment factors. PGE and REE distribution patterns are also highly similar and suggest a source from seawater. Strong variations in elemental distributions at µm-scale were observed at both sites, most likely related to intense variations in redox conditions in the sediment. The comparison with the Nick deposit highlights a stronger enrichment in Ni and Zn in the Nick deposit and a greater variety of minerals in the Niutitang shales. The PGE and REE distributions of both the Nick deposit and the Niutitang shales, however, present highly similar patterns, and support an origin from seawater. The present study provides further insight into mineralisation style and processes in these mineralised black shales, highlighting the importance of redox conditions and re-emphasizing the role of organic matter in the formation of these mineralised layers.